Prevalence and type distribution of human papillomavirus infection in women from North Sardinia, Italy - Marras Vincenzo; Capobianco Giampiero; Cocuzza Clementina; Pischedda Stefania; Castiglia Paolo; Sotgiu Giovanni; Piana Andrea; Dessole Salvatore; Muresu Elena (BMC, 2011)
Abstract Background Human papillomavirus (HPV) has been associated with several disorders of the genital tract, skin and oropharynx. The aims of our study were to evaluate the prevalence of HPV infection in women between 15 and 54 years of age in North Sardinia, Italy, to identify the prevalence of High Risk - Human papillomaviruses (HR-HPV) genotypes and to establish a correlation between molecular and cytological results. Methods From 2007 to 2009 we consecutively enrolled women aged 15-54 years admitted to public and private outpatient settings. All the participants filled in a questionnaire about the socio-cultural state, sexual activity and awareness about HPV. 323 cervical specimens were tested for HPV-DNA and HPV genotypes with INNO-LiPA HPV Genotyping CE Amp kit. Samples showing positivity to some HPV genotypes were re-tested using "in house" quantitative Real-Time PCR assays. Results Overall HPV-DNA positivity was detected in 35.9% of the women. The prevalence of HR-HPV infection among HPV positive samples was 93.1% with a specific prevalence of HPV 16, 51, 31, 53 and 18 of 54.3%, 37.9%, 10.3%, 6.9% and 5.2%, respectively. Co-infection with any HPV, HR-HPV, LR-HPV and HR/LR-HPV type was 18.3%, 14.9%, 0.9% and 2.5%, respectively; HPV 16/51 co-infection was detected in 64.6% of the HR-HPV co-infection group. The most frequent HPV-genotypes detected were 16 (32.5%) and 51 (22.7%). Among the 57 patients harboring mono-infection the most prevalent HPV genotypes were 16 (38.6%) and 31(10.5%). A multivariate analysis identified a statistical significant association between HPV infection and age and between HPV infection and previous sexual transmitted diseases. A statistically significant association between cytological cervical lesions and generic HPV exposure was identified. Conclusions To our knowledge, this is the first survey evaluating the prevalence of HPV infection in Northern Sardinia and drawing attention to the unusual high proportion of genotype HPV 51. Given the recent implementation of a widespread immunization program with vaccines not containing HPV 51, it has been relevant to prove the high prevalence of this HPV genotype from the start of the vaccination campaign, in order to avoid in the future attributing to the vaccination program a possible selection effect (HPV replacement).